Antifeedant Effect of Moringa oleifera (L.) Leaf and Seed Extract on Growth and Feeding Activity of Spodoptera litura (Fab.) (Lepidoptera: Noctuidae) - Tridiptasari, Amelia; Leksono, Amin Setyo; Siswanto, Dian (Graduate School, Universitas Brawijaya, 2019)
This study was conducted to evaluate the effect of Moringa oleifera leaf and seed extract on length, weight, and feeding activity of Spodoptera litura. Leaf and seed were extracted by maceration method in 70% ethanol. Bioassays were conducted by using five concentrations (0%, 5%, 10%, 15%, 20%) on 5 larvae by leaf-dip method with 5 times replication. The result showed that leaf and seed of Moringa extract contained alkaloid, flavonoid, and saponin which gave antifeedant effect to growth and feeding activity of larvae. The increased extract concentrations are lead to weight loss and the length shrinkage of larvae. The extracts promoted prolongation of the larval instar. Reduction of food intake of the larva is in line with the concentration increase of extracts. The antifeedant effect also affects time to stop feeding and give mortality of larvae.Keywords: antifeedant, leaf, moringa, seed, S. litura